Regulation of thyroid hormone metabolism in hyperhomocysteinemia in children living near the Chоrnobyl exclusion zone (Environment & Health, 2025)
The purpose of this study is to evaluate the regulatory relationships between homocysteine (Hcy), the folate cycle (FC) and hormones of the pituitary-thyroid axis in the body of children living near the Chоrnobyl Exclusion Zone (ChEZ).Research methods: Immunochemical, genetic, mathematical and statistical.Results. The study material included the results of genetic and laboratory testing of 336 children living near the ChEZ, in the radioactively contaminated territories of the Kyiv region of Ukraine, obtained within the framework of the implemented projects of the European Commission and the Rhone-Alpes Regional Council (France). A comprehensive correlation analysis between the Hcy indicators, vitamins B6, B9, B12, pituitary thyroid stimulating hormone (TSH), thyroxine (T4) and triiodothyronine (T3) allowed us to determine the participation of FC genes in the regulation of thyroid hormonogenesis and to reveal the pathogenesis of hyperhomocysteinemia in children. It was established that an increase in the Hcy level in the blood of the examined children occurs with a decrease in the formation of active forms of vitamins B9 and B12 in FC. The metabolism of thyroid hormones in peripheral tissues occurs with the participation of FC and Hcy. An increase in the Hcy content in the blood leads to the activation of the T4 deiodination process and an increase in the formation of T3. In turn, T3, having a stimulating effect on the enzyme systems of FC, promotes the enhancement of the process of formation of 5-MTHF, which plays a major role in the methylation of Hcy and the formation of internal methionine. At the same time, the activity of the process of T4 deiodination in peripheral tissues decreases, which leads to a decrease in the formation of T3.Conclusions. When assessing the thyroid status, attention should be paid to the process of T4 utilization, while usually attention is paid to the process of its production by the thyroid gland. Under conditions of radiation exposure, a decrease in the level of T4 in the blood should be considered from the standpoint of a violation of Hcy metabolism. An increase in the formation of T3 is associated with the need to adapt the body to environmental conditions.
Keywords: homocysteine; pituitary-thyroid axis hormones; folate cycle genes; children; Chоrnobyl Exclusion Zone; radioactively contaminated areas